2013
DOI: 10.1021/jm4001538
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure–Activity Relationship Studies of Novel 3-Alkylindole Derivatives as Selective and Highly Potent Myeloperoxidase Inhibitors

Abstract: Due to its production of potent antimicrobial oxidants including hypochlorous acid, human myeloperoxidase (MPO) plays a critical role in innate immunity and inflammatory diseases. Thus MPO is an attractive target in drug design. (Aminoalkyl)fluoroindole derivatives were detected to be very potent MPO inhibitors; however, they also promote inhibition of the serotonin reuptake transporter (SERT) at the same concentration range. Via structure-based drug design, a new series of MPO inhibitors derived from 3-alkyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…Recently a number of direct specific MPO inhibitors have been developed. These include PF-1355 (2-(6-(2,5-dimethoxyphenyl)-4-oxo-2-thioxo-3,4-dihydropyrimidin-1(2H)-yl)acetamide) (Zheng et al, 2015) and MPOi-II (4-(5-fluoro-1H-indol-3-yl)butanamide) (Soubhye et al, 2013). As expected, both of these inhibitors dramatically reduced MPO activity in NB4 cells (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a number of direct specific MPO inhibitors have been developed. These include PF-1355 (2-(6-(2,5-dimethoxyphenyl)-4-oxo-2-thioxo-3,4-dihydropyrimidin-1(2H)-yl)acetamide) (Zheng et al, 2015) and MPOi-II (4-(5-fluoro-1H-indol-3-yl)butanamide) (Soubhye et al, 2013). As expected, both of these inhibitors dramatically reduced MPO activity in NB4 cells (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MPO has become a target of interest for novel anti-inflammatory drug development (Malle et al, 2007), and a number of potent specific MPO inhibitors were recently reported (Tidén et al, 2011; Forbes et al, 2013; Soubhye et al, 2013, 2016; Li et al, 2015; Zheng et al, 2015). We have used two such inhibitors, PF1355 and MPOi-II, and show that like SA, they reduce etoposide- and mitoxantrone-induced damage in MPO-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in this instance, a direct correlation between IC 50 values and docking scores could not generally be obtained through the use of conventional docking programs. 34 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in important work by Brennan and coworkers in MPO knock out mice, revealed that NT formation in acute inflammation models is largely MPO-dependent [119], consistent with the influx and degranulation of activated neutrophils in the inflammatory sites. MPO-mediated nitration pathways can be further distinguished, by using specific MPO- inhibitors [120] such as alkyl indole derivatives [121]. …”
Section: Peroxynitrite Footprintsmentioning
confidence: 99%